Outcome and characteristics of non‐measurable myeloma: A cohort study with population‐based data from the Swedish Myeloma Registry. (22nd February 2020) - Wålinder, Göran; Samuelsson, Jan; Näsman, Per; Hansson, Markus; Juliusson, Gunnar; Forsberg, Karin; Svensson, Ronald; Linder, Olle; Carlson, Kristina; Kristinsson, Sigurdur Y.; Mellqvist, Ulf Henrik; Hveding Blimark, Cecilie; et al.
Abstract: Objective: We describe survival in patients with oligo‐ and non‐secretory multiple myeloma (MM). We refer to the whole group as non‐measurable MM and compare it with secretory MM. Methods: Oligo‐secretory MM was defined as M protein in serum <10 g/L and M protein in urine <200 measured as mg/day, mg/liter or mg/mmol creatinine. If patients had no M protein, they were defined as non‐secretory. The groups were also subdivided by Free Light Chains (SFLC) level and ratio. Results: Out of 4325 patients with symptomatic MM in the Swedish Myeloma Registry during 2008‐2016 eligible for the study, 389 patients (9%) had non‐measurable MM. Out of these, 253 patients (6%) had oligo‐secretory and 136 (3%) had non‐secretory MM. Median survival for secretory MM was 42.7 months, non‐measurable MM 40.2 months, oligo‐secretory MM 38.6 months, and non‐secretory MM 44.6 months. Difference in overall observed survival was non‐significant for all groups when compared with secretory MM. Within non‐secretory MM, stem cell transplantation (SCT), 95% being auto‐SCT, was significant for superior survival in multivariate analysis (HR 0.048. P  = .0015). Conclusion: In this population‐based study, we found no difference in survival between oligo‐ or non‐secretory MM when compared with secretory MM. SCT appears to be important also for patients with non‐secretory disease.